Knowledge, attitude, and practices toward food safety among students in Bangladesh: A cross-sectional web-based study. Issue 4 (April 2023) - Ali, Md Taif; Mahmud, Sultan; Mohsin, Md; Mian, Ashraf Uddin; Islam, Ariful; Ahmed, Fee Faysal
Abstract: Background: Foodborne diseases are a preventable but under-reported public health issue. These illnesses are a public health concern and contribute significantly to healthcare costs. People must understand how their knowledge, attitudes, and practices affect food safety and how they can reduce the risk of foodborne illness. This study aimed at investigating the current situation of knowledge, attitudes, and practices toward food safety among Bangladeshi students and identifying the determinants of having adequate knowledge, favorable attitudes, and good practices. Methods: The research is based on a cross-sectional anonymous online survey that took place from January 1st to February 15th, 2022. Participants in this survey had to be at least 8th-grade students enrolled in Bangladeshi institutions. Upon description of the study's aim, the questionnaire's concept, assurances regarding respondents' confidentiality, and the study's voluntary nature, informed consent was taken from each participant before starting the survey. Descriptive statistics, Chi-square test, and logistic regression were used to explore the knowledge, attitudes, and practices of students and identify factors affecting them using the statistical software STATA. Results: A total of 777 students participated in the study, the majority of them were male (63.96%) and aged between 18 and 25 years (60%). Almost half of the respondents were at the undergraduate level and less than half of the participants (45%) lived with their families. Among the participants, around 47% had adequate knowledge, 87% had favorable attitudes, and only 52% had good practices toward food safety. Female students, students having a food safety course/training, and students whose mothers were educated had significantly higher knowledge of food safety. Besides, students at higher education levels, students having a food safety course/training, and students with educated mothers displayed significantly higher odds of possessing favorable attitudes toward food safety. Similarly, female students, having a food safety course/training, students at higher education levels, and students with educated mothers were significantly associated with good practices toward food safety among students. Conclusion: The study shows that students in Bangladesh lack knowledge of food safety and have poor practices toward food safety. For the student population of Bangladesh, more systematic and targeted food safety education and training are required.